TDP-43 promotes tau accumulation and selective neurotoxicity in bigenic Caenorhabditis elegans - Caitlin S. Latimer; Jade G. Stair; Joshua C. Hincks; Heather N. Currey; Thomas D. Bird; C. Dirk Keene; Brian C. Kraemer; Nicole F. Liachko (The Company of Biologists, 2022)
Although amyloid β (Aβ) and tau aggregates define the neuropathology of Alzheimer's disease (AD), TDP-43 has recently emerged as a co-morbid pathology in more than half of patients with AD. Individuals with concomitant Aβ, tau and TDP-43 pathology experience accelerated cognitive decline and worsened brain atrophy, but the molecular mechanisms of TDP-43 neurotoxicity in AD are unknown. Synergistic interactions among Aβ, tau and TDP-43 may be responsible for worsened disease outcomes. To study the biology underlying this process, we have developed new models of protein co-morbidity using the simple animal Caenorhabditis elegans. We demonstrate that TDP-43 specifically enhances tau but not Aβ neurotoxicity, resulting in neuronal dysfunction, pathological tau accumulation and selective neurodegeneration. Furthermore, we find that synergism between tau and TDP-43 is rescued by loss-of-function of the robust tau modifier sut-2. Our results implicate enhanced tau neurotoxicity as the primary driver underlying worsened clinical and neuropathological phenotypes in AD with TDP-43 pathology, and identify cell-type specific sensitivities to co-morbid tau and TDP-43. Determining the relationship between co-morbid TDP-43 and tau is crucial to understand, and ultimately treat, mixed pathology AD.